“The Tahiti of the Northern Hemisphere”: Countertransference as Impediment to Transculturalism in Audrey Magee’s The Colony (2022) - Ní Éigeartaigh, Aoileann (TransCulturale, 2024)
Victor Turner suggests that travel is an intrinsically liminal experience, detaching the traveller from the structures of their normal lives and immersing them in an unfamiliar, perhaps even incomprehensible, environment. In theory, this suspension in unfamiliar spaces should invite a willingness to embrace the different perspectives one encounters, thus expanding one’s mind. The difficulty, as Georges Devereux argues, is that the observer rarely succeeds in adopting an objective gaze when confronted with an unfamiliar culture. Rather that gaze is structured by their own expectations, resulting in the imposition of meaning on what is observed, a process he describes as “countertransference”. This essay will analyze the difficulties identified by Devereux in constructing a genuinely transcultural perspective, using as a case study Audrey Magee’s novel The Colony (2022).